Impact of Psychological Stress on Pain Perception in an Animal Model of Endometriosis. (October 2017) - Hernandez, Siomara; Cruz, Myrella L.; Seguinot, Inevy I.; Torres-Reveron, Annelyn; Appleyard, Caroline B.
Purpose: Pain in patients with endometriosis is considered a significant source of stress but does not always correlate with severity of the condition. We have demonstrated that stress can worsen endometriosis in an animal model. Here, we tested the impact of a psychological stress protocol on pain thresholds and pain receptors. Methods: Endometriosis was induced in female rats by suturing uterine horn tissue next to the intestinal mesentery. Sham rats had sutures only. Rats were exposed to water avoidance stress for 7 consecutive days or handled for 5 minutes (no stress). Fecal pellets and serum corticosterone (CORT) levels were measured as an index of anxiety. Pain perception was assessed using hot plate and Von Frey tests. Substance P, enkephalin, endomorphin-2, Mu opioid receptor (MOR), and neurokinin-1 receptor expression in the spinal cord were measured by immunohistochemistry. Results: Fecal pellets and CORT were significantly higher in the endo-stress (ES) group than endo-no stress (ENS; P < .01) and sham-no stress groups (SNS; P < .01). The ES rats had more colonic damage ( P < .001 vs SNS; P < .05 vs ENS), vesicle mast cell infiltration ( P < .01 vs ENS), and more severe vesicles than ENS. The ES developed significant hyperalgesia ( P < .05) but stress reversed the allodynic effect caused by endo ( P < .001). The MOR expression was significantly reduced in ENS versus SNS ( P < .05) and more enkephalin expression was found in endo groups. Conclusion: Animals subjected to stress develop more severe symptoms but interestingly stress seems to have beneficial effects on abdominal allodynia, which could be a consequence of the stress-induced analgesia phenomenon.